2017
DOI: 10.18517/ijaseit.7.5.2278
|View full text |Cite
|
Sign up to set email alerts
|

Macro-Factor Affecting the Electricity Load Demand in Power System

Abstract: As a developing country, Malaysia is expected an increment on their electricity consumption align with growing of economy, population as well as industrial demands. For that reason, this paper brings an analysis that considered some macro factors identified as geographical parameters, meteorological parameters, and economic parameters which believed will effect the demand in electricity over the country. However, the case study for this research is focusing the demands in the area named Johor Bahru and Skudai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Electricity, as a form of energy, has assumed a prime position as a major energy resource for mankind globally [1], [2]. An unrelenting increase in the human activities and desires have brought about continuous transcendence in the importance of electricity in most societies, even compared to other energy resources which are still in use such as charcoal and labour intensive efforts [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electricity, as a form of energy, has assumed a prime position as a major energy resource for mankind globally [1], [2]. An unrelenting increase in the human activities and desires have brought about continuous transcendence in the importance of electricity in most societies, even compared to other energy resources which are still in use such as charcoal and labour intensive efforts [3].…”
Section: Introductionmentioning
confidence: 99%
“…From an analytical study, the approximate sum total of generation capacity, according to [10], is 5,000 MW to serve total population of 191,835,936 [11]. Hence, using (1): Looking at this analysis, it is observed that evenly distributed power supply to every inhabitant will be at 26.064 W, which is just enough to power up a highly efficient light bulb (for example, light emitting diode (LED) bulb, or compact fluorescent lamp (CFL)). The analysis above has not even considered the influence of the process driven and manufacturing industries and energy loss due to theft stated in [12].…”
Section: Introductionmentioning
confidence: 99%